Impact of Changing Cropping Pattern on Man-animal Conflicts around Gir P.A. with Specific Reference to Talala Taluka - Vijayan, S.; Pati, B. P. (Indian Forester, 2001)
The Gir National Park is surrounded by seven Talukas of two Districts. Main occupation of the villagers in this area is farming due to fertile black soil and good irrigation facility. Farmers are changing to sugarcane (87% increase in 10 years) and Mango cultivation (103%) leaving their old traditional crops like groundnut. Wheat etc, as the former fetch good money in local market. Large-scale cultivation of Sugarcane and Mango orchard in peripheral villages of Gir National Park and Sanctuary has given rise to a thick growth of an artificial dense cover. This attracts large carnivores like Lion (Panthera leo persica) and Leopard (Panthera pardus) to take shelter, raise their young and stalk domestic animals as well as wild animals like Wild boar (Sus scrofa). The straying incidences of Lions and Leopards increased to 411 % and 386% respectively from last 3 years (from 1997). This study reveals than in Talala Taluka 72% (13 incidences) and 59% (16 incidences) of the total attacks by Lions and Leopards respectively took place in farmland. In addition to this livestock kill is on increase in farmland (28% increase in 5 years). These encounters have given rise to antagonist attitude among farmers towards the big cats and they have in some cases retaliated by poisoning the carcass. The presence of big cats in farmlands has given rise to fear psychosis among labourers and in turn affects the harvesting of crops and results in loss of man-days and money. More and more requests are received by the Wildlife Rescue Team of the Forest Department for capturing and relocating the big cats from farmlands to its original forest area.